Law Enforcement Against Unauthorized Access to Security Restricted Area (A Study at Sepinggan Airport Balikpapan) - Rahman, Luthfi Ahmadani; Lisi, Ivan Zairani; Hairan, Hairan (IHSA Institute, 2025)
This study examines law enforcement against individuals who enter the Security Restricted Area without authorization at Sultan Aji Muhammad Sulaiman Sepinggan Airport in Balikpapan. The research identifies five contributing factors to the violations: the change in status of certain areas from Security Restricted Area to Controlled Area; substandard perimeter fencing conditions; inconsistent entry permit checks by aviation security personnel; low public awareness—with 79% of respondents unaware of the definition of a Security Restricted Area and 84% unaware of the penalties for violations; and the historical and economic background of fishermen who have inhabited the area since 1975. Although regulations stipulate penalties for violators, in practice law enforcement is has been well to verbal warnings without firm criminal sanctions. Barriers to enforcement include a lack of assertiveness from aviation security personnel who are still permissive, and insufficient public dissemination of regulations. The study recommends enhanced supervision, strengthened regulatory frameworks, and public education to improve the effectiveness of law enforcement in ensuring aviation security